Coanda effect : flow phenomenon and applications - Ahmed, Noor A. (New York, NY : CRC Press/Taylor & Francis Group, 2019)
"Coanda effect is a complex fluid flow phenomenon enabling the production of vertical take-off/landing aircraft. Other applications range from helicopters to road vehicles, from flow mixing to combustion, from noise reduction to pollution control, from power generation to robot operation, and so forth. Book starts with description of the effect, its history and general formulation of governing equations/simplifications used in different applications. Further, it gives an account of this effect's lift boosting potential on a wing and in non-flying vehicles including industrial applications. Finally, occurrence of the same in human body and associated adverse medical conditions are explained"--
OCLC-licensed vendor bibliographic record.
Keywords: Fluidics; Coanda effect -- Industrial applications; Coanda effect -- Scientific applications; Aeronautics; Hydraulic engineering; Body fluid flow; SCIENCE / Physics; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Mechanical